Concept of Regulating The Mechanism For Deleting Personal Data And Deleting Indexes In Order To Ensure Legal Certainty - Anas Rafi Prakasya; Patricia Audrey Ruslijanto; Rachmi Sulistyarini (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Digital transformation has accelerated the massive use of personal data in various sectors, including government, business, health, and public services. However, the increasing use of digital systems also raises risks of data breaches, misuse of information, and the persistence of harmful digital footprints. This study analyzes the legal regulation of personal data erasure and de-indexing mechanisms in Indonesia and examines the extent to which these mechanisms provide legal certainty for data subjects and data controllers. The research employs a normative juridical method using statutory, conceptual, and comparative approaches. The study finds that Indonesia has recognized the right to erasure and the right to delisting through the ITE Law, Government Regulation Number 71 of 2019, and Law Number 27 of 2022 concerning Personal Data Protection. Nevertheless, implementation remains problematic due to fragmented regulations, unclear procedural standards, limited institutional oversight, and the absence of comprehensive implementing regulations. Therefore, regulatory harmonization, the establishment of independent supervisory institutions, clear procedural mechanisms, and increased public digital literacy are essential to ensure effective personal data protection and legal certainty in Indonesia.